2018
DOI: 10.1177/0300060518765333
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of fluocinolone acetonide 0.025% otic solution in patients with otic eczema: a randomized, double-blind, placebo-controlled clinical trial

Abstract: ObjectivesTo assess the efficacy and safety of fluocinolone acetonide 0.025% otic solution versus placebo in treating patients with otic eczema.MethodsIn this multicentre, randomized, double-blind, parallel-group phase 3 clinical trial, conducted at 12 Spanish centres between March 2012 and March 2013, patients received fluocinolone acetonide 0.025% or placebo otic solution twice daily for 7 days (days 1–7) with an 8-day follow-up (days 9–15). Outcome measures included change in itching from baseline (day 1) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Among the identified phenolic compounds, Zhebeiresinol a phenolic lignan has potential health benefits, including antioxidant and anti-inflammatory properties [33]. The compound Fluocinolone has been studied for treating localized psoriasis [34]. Furthermore Eudesmin is found in LC-QTOF/MS result, which is natural phenolic lignan having specific antioxidant and anti-inflammatory potential [35], while Clausarinol, Chamuvaritin and To-mentolide A seemed to be a new compounds with limited or no prior study.…”
Section: Discussionmentioning
confidence: 99%
“…Among the identified phenolic compounds, Zhebeiresinol a phenolic lignan has potential health benefits, including antioxidant and anti-inflammatory properties [33]. The compound Fluocinolone has been studied for treating localized psoriasis [34]. Furthermore Eudesmin is found in LC-QTOF/MS result, which is natural phenolic lignan having specific antioxidant and anti-inflammatory potential [35], while Clausarinol, Chamuvaritin and To-mentolide A seemed to be a new compounds with limited or no prior study.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients even go to the emergency room (ER) for symptoms such as severe itching, or even hearing loss due to occlusion of the ear canal. Treatment with topical corticosteroids, 2 associated with topical antibiotics 3 are the most frequent prescription. However, its use is normally limited to 7 days.…”
Section: Figurementioning
confidence: 99%
“…Results indicated that patients treated fluocinolone acetonide solutions (n= 58), compared with the placebotreated group (n= 63), had significantly higher reduction in itching (P < 0.001) and improvement in otoscopic signs (P < 0.001). (21) We have investigated the option of using Flixonase ® topically in 25 resistant cases. As presented in the section above, all cases who returned to follow up were classified as being cured and symptoms free.…”
Section: Discussionmentioning
confidence: 99%